Regulatory Challenges and Legal Safeguards in Online Lending: Insights from OJK Regulation No. 10 of 2022 - Wijaya, Bagas Satria; B, Erlina (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
Online loan agreements are an innovation in digital financial services that offer ease of access and speed in transaction processes. However, this service also presents several challenges, such as the risk of personal data breaches and the widespread occurrence of illegal online lending. This study aims to examine online loan agreements based on the Financial Services Authority (OJK) Regulation Number 10 of 2022 concerning information technology-based joint funding services. The research employs a normative juridical approach through literature review and doctrinal analysis. The findings highlight the importance of digital financial literacy in helping the public understand their rights and obligations in online loan agreements. OJK regulations provide a legal framework for consumer protection, both preventively and repressively, including strict sanctions for violations. The synergy between public education and strong law enforcement is key to creating a safe, trustworthy, and sustainable online lending ecosystem.